find roots of2x^2+x+4=0 by quadratic formula
Answers
Answered by
0
Solving 2x2-x-4 = 0 by Completing The Square .
Divide both sides of the equation by 2 to have 1 as the coefficient of the first term :
x2-(1/2)x-2 = 0
Add 2 to both side of the equation :
x2-(1/2)x = 2
Now the clever bit: Take the coefficient of x , which is 1/2 , divide by two, giving 1/4 , and finally square it giving 1/16
Add 1/16 to both sides of the equation :
On the right hand side we have :
2 + 1/16 or, (2/1)+(1/16)
The common denominator of the two fractions is 16 Adding (32/16)+(1/16) gives 33/16
So adding to both sides we finally get :
x2-(1/2)x+(1/16) = 33/16
Adding 1/16 has completed the left hand side into a perfect square :
x2-(1/2)x+(1/16) =
(x-(1/4)) • (x-(1/4)) =
(x-(1/4))2
Things which are equal to the same thing are also equal to one another. Since
x2-(1/2)x+(1/16) = 33/16 and
x2-(1/2)x+(1/16) = (x-(1/4))2
then, according to the law of transitivity,
(x-(1/4))2 = 33/16
We'll refer to this Equation as Eq. #3.2.1
The Square Root Principle says that When two things are equal, their square roots are equal.
Note that the square root of
(x-(1/4))2 is
(x-(1/4))2/2 =
(x-(1/4))1 =
x-(1/4)
Now, applying the Square Root Principle to Eq. #3.2.1 we get:
x-(1/4) = √ 33/16
Add 1/4 to both sides to obtain:
x = 1/4 + √ 33/16
Since a square root has two values, one positive and the other negative
x2 - (1/2)x - 2 = 0
has two solutions:
x = 1/4 + √ 33/16
or
x = 1/4 - √ 33/16
Note that √ 33/16 can be written as
√ 33 / √ 16 which is √ 33 / 4
IF U LIKE REVIEW THANKS AND COMMENT ALSO MARK AS A BRAINLIEST ANSWER
Divide both sides of the equation by 2 to have 1 as the coefficient of the first term :
x2-(1/2)x-2 = 0
Add 2 to both side of the equation :
x2-(1/2)x = 2
Now the clever bit: Take the coefficient of x , which is 1/2 , divide by two, giving 1/4 , and finally square it giving 1/16
Add 1/16 to both sides of the equation :
On the right hand side we have :
2 + 1/16 or, (2/1)+(1/16)
The common denominator of the two fractions is 16 Adding (32/16)+(1/16) gives 33/16
So adding to both sides we finally get :
x2-(1/2)x+(1/16) = 33/16
Adding 1/16 has completed the left hand side into a perfect square :
x2-(1/2)x+(1/16) =
(x-(1/4)) • (x-(1/4)) =
(x-(1/4))2
Things which are equal to the same thing are also equal to one another. Since
x2-(1/2)x+(1/16) = 33/16 and
x2-(1/2)x+(1/16) = (x-(1/4))2
then, according to the law of transitivity,
(x-(1/4))2 = 33/16
We'll refer to this Equation as Eq. #3.2.1
The Square Root Principle says that When two things are equal, their square roots are equal.
Note that the square root of
(x-(1/4))2 is
(x-(1/4))2/2 =
(x-(1/4))1 =
x-(1/4)
Now, applying the Square Root Principle to Eq. #3.2.1 we get:
x-(1/4) = √ 33/16
Add 1/4 to both sides to obtain:
x = 1/4 + √ 33/16
Since a square root has two values, one positive and the other negative
x2 - (1/2)x - 2 = 0
has two solutions:
x = 1/4 + √ 33/16
or
x = 1/4 - √ 33/16
Note that √ 33/16 can be written as
√ 33 / √ 16 which is √ 33 / 4
IF U LIKE REVIEW THANKS AND COMMENT ALSO MARK AS A BRAINLIEST ANSWER
Similar questions